System CAT (Computer Assisted Test) information for Multimedia Department of Muhammadiyah Vocational High School 2 Moyudan Web-based - Amalia K, Rizka; Wahana, Aditya; Wardani, Setia (APPLIED SCIENCE AND TECHNOLOGY REASERCH JOURNAL, 2023)
The computer-assisted test or what is usually called the CAT is a test whose main media use is a computer and the internet. The CAT system is the same as the test in general, it's just that the difference is the media used. If usually the CAT test still uses paper, then in this system this is no longer needed. SMK Muhammadiyah 2 Moyudan is located at Ngentak , Sumberagung , Kec . Moyudan , Sleman Regency, Special Region of Yogyakarta 55563. The process of accepting students majoring in multimedia tests that are still carried out manually, namely using paper and other writing instruments, certainly takes a long time. The purpose of this study is to design a CAT system so that the tests carried out can be efficient and the resulting values can be obtained in real-time. This system is designed using the Laravel framework. PHP and MySQL databases are the programming languages used in this study.